2018
DOI: 10.1007/s12325-018-0710-4
|View full text |Cite
|
Sign up to set email alerts
|

An Early View of Real-World Patient Response to Sacubitril/Valsartan: A Retrospective Study of Patients with Heart Failure with Reduced Ejection Fraction

Abstract: Novartis Pharmaceuticals Corporation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 13 publications
4
23
1
1
Order By: Relevance
“…As observed from the PARADIGM sub-analysis by Jhund PS et al, when the authors assessed the efficacy and safety of sacubitril-valsartan by age, they found that the superiority of sacubitril-valsartan over enalapril persisted across all age groups including the elderly, though the same efficacy gap decreased slightly in the older population. 34 The clinical importance of these data is that they reinforce the positive observations from the clinical trial data, 1,33,35 and the emerging real world data, 14,15,17 and indicate that the majority of the cohort of community patients can tolerate the agent and benefit from the compound, in terms of either a reduction in NT-proBNP or an improvement in LVEF. More importantly, these data support the importance of achieving maximum dose and link this to a reduction in diuretic use, establishing clinical volume assessment as a critical feature in using this agent.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…As observed from the PARADIGM sub-analysis by Jhund PS et al, when the authors assessed the efficacy and safety of sacubitril-valsartan by age, they found that the superiority of sacubitril-valsartan over enalapril persisted across all age groups including the elderly, though the same efficacy gap decreased slightly in the older population. 34 The clinical importance of these data is that they reinforce the positive observations from the clinical trial data, 1,33,35 and the emerging real world data, 14,15,17 and indicate that the majority of the cohort of community patients can tolerate the agent and benefit from the compound, in terms of either a reduction in NT-proBNP or an improvement in LVEF. More importantly, these data support the importance of achieving maximum dose and link this to a reduction in diuretic use, establishing clinical volume assessment as a critical feature in using this agent.…”
Section: Discussionmentioning
confidence: 61%
“…Real world data to complement this impressive clinical trial information are of importance to assess whether response is similar in a community population, who are invariably older and with more comorbidities . To date, the limited published real world data indicate a similar positive experience . Notably however, achievement of TD of sacubitril‐valsartan appears to be more of a challenge in the community.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Biorąc pod uwagę rzeczywiste dane w zakresie kosztów terapii w warunkach rzeczywistej praktyki klinicznej wśród 200 chorych z HFrEF w Stanach Zjednoczonych [20], wykazano, że stosowanie Entresto TM obniżyło koszty opieki zdrowotnej u pacjentów z HF. Stosowanie sakubitrilu/walsartanu wiązało się z poprawą stanu zdrowia i zmniejszeniem liczby hospitalizacji w ciągu 4 miesięcy od rozpoczęcia leczenia tym lekiem.…”
Section: Kontynuacja Leczenia I Jego Monitorowanieunclassified